The role of the openings in the out-of-plane behaviour of masonry infill walls - André Furtado (2021)
This research work aims to present an experimental study concerning the effect of the openings in the out-of plane (OOP) behaviour of masonry infills in RC buildings. The experimental campaign comprises the OOP testing of three full-scale infill walls made up of horizontal hollow clay bricks, two of them with a central window and the remaining one with a central door. One of the specimens with a central opening was first subjected to a previous in-plane test and, after that, the damaged wall was subjected to an OOP test. All the tests consisted of applying a loading-unloading-reloading history of imposed displacements in the OOP direction through a uniformly distributed load. An innovative setup was used and adapted for each wall typology. The results are presented in terms of OOP force-displacement responses, damage evolution, relative stiffness and energy dissipation capacity. Finally, the test results are compared to each other to assess the effect of: i) the area of the opening; and ii) the previous damage. It was found that the openings reduced the maximum strength of 30% for undamaged panels, and it occurred for lower displacement demands. The increase of the opening area did not affect the peak load; however, it reduced their energy dissipation capacity significantly. The energy dissipation capacity reduced from 42% to 70%.